MODERN APPROACHES TO THE USAGE OF INFORMATION TECHNOLOGIES IN TEACHING ENGLISH TO FUTURE PHILOLOGISTS - Dmytro Yu. Sharyi (Інформаційні технології і засоби навчання, 2013)
The article deals with the highlighting of the problem of modern approaches to information technologies usage in teaching English to future philologists. The usage of these technologies in the process of formation of professional competence of students of linguistic specialties is conditioned by the necessity of education modernization and working out new strategies of its development as well as realization of grounded changes in higher education strategies. Such aspects of multimedia technologies usage in the educational process as students’ individual work, teaching different kinds of speech activity, control at English classes are studied in the paper. Attention is focused on the necessity of information technologies usage for increasing effectiveness of the educational process.